Regulation and optimization of cultivated land in different ecological function areas under the guidance of food security goals-a case study of Mengjin County, Henan Province, China - Guan, Xiaoke; Wang, Xiuli; Zhang, Jiaqi; Dai, Zhiming (Frontiers in Environmental Science, 2023)
China's arable land is facing the dual constraints of increasing "non-grain" and tightening ecological control. However, extreme emphasis on food production or excessive attention to ecological protection cannot effectively solve the practical problems of cultivated land utilization. In this paper, evaluation indexes were selected from the aspects of ecological service, landscape integrity, ecological sensitivity, etc., and ecological importance evaluation system for territory space was constructed. The ecological importance of territorial space was divided into three ecological functional areas, namely, the extremely important regions, the relatively important regions and the general regions. The morphological characteristics of cultivated land use in different ecological function areas were described systematically, and the main problems of cultivated land use in different regions were analyzed. On the basis of ensuring the ecological security of territorial space, this paper puts forward the regulation and control plan of cultivated land in different ecological functional areas aiming at food security, and makes an empirical study with Mengjin County as the case area. The results showed that: under the guidance of food security objectives, the implementation of different types of cultivated land remediation programs according to the problems existing in different ecological functional areas could guarantee food security to the greatest extent and amplify the ecological and environmental effects of land remediation. By means of land consolidation and ownership adjustment, the abandoned farmland in general and relatively important ecological regions can be restored for food use, which can not only enhance the food supply capacity, but also without causing damage to the ecological environment. There is a large area of arable land in the ecologically extremely important regions. Large-scale ecological conversion will have a certain impact on food security supply. Promoting ecological farming is an important way to resolve the contradiction between food safety production and ecological environment protection. This study can provide reference for decision making of arable land consolidation in the new period.